Identity Contested: Cultural Resilience in the Midst of Islamization of Politics - Yanwar Pribadi (Al-Jami'ah: Journal of Islamic Studies, 2018)
Local-level leaders in contemporary Indonesia have involved in the country’s turbulent politics. The regent of Purwakarta (2008-2018), Dedi Mulyadi, employed, for the most part, culture-based political preferences develop his territory. In doing so, he frequently encountered with various forms of Islamization of politics, hindering his strategies to reach his individual goals, to display his socio-political identity, and to socio-culturally empower cultural resilience. The regent appeared to challenge rampant Islamization of politics by “waging the war” against Islamist groups in the name of Sundanese indigenous culture. This paper seeks to explore recent developments of the relationships between Islam and local culture in Indonesia with the case study of Purwakarta in particular and West Java in general, and how a local-level leader was able to optimize his potentials to empower cultural resilience in the midst of Islamization of politics. This paper also investigates the complex landscape of these relationships in an effort to map out the various forces at play and shows that by investigating the interplay between religion, culture, and other entities, a key driver local level played pivotal roles in his ways of defining ethnic identity, creating authority, and empowering cultural resilience. [Terdapat beberapa pemimpin daerah terlibat dinamika politik nasional dewasa ini. Dedi Mulyadi, Bupati Purwakarta periode 2008-2018, termasuk salah satu tokoh yang membangun daerah dengan berbasis pada budaya lokal. Bersamaan dengan itu, ia sering berhadapan dengan sejumlah gerakan Islam politik dalam menghambat tujuan pertahanan identitas sosio-politik dan memberdayakan ketahanan bentuk budaya lokal. Sang bupati tampil dengan identitas budaya lokal Sunda dalam rangka menghadapi tantangan Islamisasi politik dari kelompok-kelompok Islamis yang ‘mengobarkan perang’ kemana mana. Tulisan ini membahas perkembangan terkini hubungan antara Islam dan budaya lokal di Indonesia dengan studi kasus Purwakarta dan Jawa Barat. Kinerja pemimpin daerah ini mampu mempertahankan budaya lokal di tengah arus Islamisasi politik. Tulisan ini menginvestigasi kompleksitas konteks hubungan-hubungan tersebut dalam usaha pemetakan kekuatan yang bermain pada investigasi tumpang tindih antara agama, budaya, dan entitas-entitas lain. Hal ini berkenaan dengan tokoh penggerak tingkat lokal memainkan peran penting dalam makna identitas etnis, penciptaan otoritas, dan ketahanan budaya lokal.]